PECULIARITIES OF PATRIOTIC EDUCATION OF THE GROWING GENERATION AT THE PRESENT STAGE - Tatiana Aleksandrovna Yudina; Svetlana Evgenievna Belovodova (Современная наука и инновации)
The relevance of this study lies in the uniqueness of the social situation of development that has developed for the younger generation, that the old landmarks and values of society have already lost their significance for them, and the new ones have not yet developed.